Milk Production and Reproductive Performance of Holstein Friesian Dairy Cattle in the Working Area of ​​South Bandung Pangalengan Animal Husbandry Cooperative (KPBS) Bandung Regency - Tendy Kusmayadi; Ibrahim Hadist (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
Increasing the population and productivity of dairy cows is one of the way to boost national milk production capacity. This study was aimed to determine and investigate the performance of milk production and reproduction of Friesian Holstein (FH) dairy cows in the Working Area of KPBS Pangalengan, Bandung Regency. This research used FH dairy cows with a complete milk production and reproduction record. In total, there were 90 heads of cows in the Pangalengan District and 178 heads of cows in the Kertasari District. This study used the survey method to collect the data. A Multistage Random Sampling Method was used in this research. Sampling was carried out in two stages, the first stage was sampling from two sub-district locations in Pangalengan and Kertasari Districts. In the second stage, two villages were selected from each district: Pangalengan and Margamukti Villages in Pangalengan District, and Santosa and Tarumajaya Villages in Kertasari District. Farmers and their cows were chosen by simple random sampling. Data on milk production and reproduction records were obtained from farmers and their cows through direct observation and interviews related to the identity of the cattle they owned. The results showed that the average performance of the milk production characteristics of FH dairy cows was: an average milk production of 3779.2±497.48 liters/head/day, an average length of lactation of 307.8±31.30 days, and an average dry period of 72.14±21.43 days. The lactation period had a significant effect (P<0.05) on milk production. The peak of milk production was reached in the fourth lactation period. The mean of reproductive traits consisting of the first postpartum mating was 77±20.5 days, the average length of days open was 96±26.4 days, the average number of services per conception was 1.8±0.85 times, and the average calving interval was 381.05± 24.5 days. In conclusion, FH dairy cows raised in Pangalengan and Margamukti Villages, Pangalengan District, Santosa and Tarumajaya Village, Kertasari District, in the working area of Pangalengan KPBS during the Covid-19 pandemic indicated a fairly good performance of milk production and reproduction characteristics.